(untitled) (Revista Argentina de Musicología, 2020)
Nowadays, the Japanese end-blown flute shakuhachi (尺八) has a presence throughout the world, in many musical genres. The distinctive features of its sound are product of its use for centuries as a religious implement, that is, as a hōki (法器), associated with Buddhist practices. However, during the Meiji period (1868-1912) of the history of Japan, this use was restricted significantly, to become in an instrument to be aesthetically appreciated, that is, in a gakki (楽 器), despite of which it retained many of its previous attributes. The objective of this work is to identify the processes through which the shakuhachi went from being an element of the spiritual life of a group of monks to being part of diverse musical practices of wider sectors. It will be seen that this was due to governmental intervention, the participation of new interpreters and the exposure of the Japanese to foreign music. The changes in the construction of the instrument, the characteristics of the repertoire, the interpretation techniques, the social function of masters and performers, and the forms of knowledge transmission will be taken into account.